Descriptions - Neale, Stephen, 1958- (Cambridge, Mass. : MIT Press, 1990)
In 1905, Bertrand Russell argued that certain logical puzzles are solved if definite descriptions are treated as quantified expressions rather than referential expression, as Frege had thought. Since then, philosophers and, more recently, linguists have debated the relevance of this paradigm to the study of the semantics of natural language. In Descriptions, Stephen Neale provides the first sustained defense and extension of Russell's theory, placing it in the center of a theory of singular and nonsingular descriptive phrases and anaphoric pronouns -- Provided by the publisher.
Introduction -- The Theory of Descriptions -- Context and Communication -- Scope, Substitutivity, and Opacity -- Pronouns and Anaphora -- Further Notes on Descriptive Anaphora.
"A Bradford book."
Includes bibliographical references (pages 269-281) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Language and languages -- Philosophy; Description (Philosophy); Anaphora (Linguistics); Description (Philosophie); Anaphore; Langage et langues -- Philosophie; descriptions (documents); descriptive note; description (activity); PHILOSOPHY -- Epistemology; Anaphora (Linguistics); Description (Philosophy); Language and languages -- Philosophy; Anapher; Deskriptive Linguistik; Kennzeichnung; Sprachphilosophie; Natuurlijke taal; Semantiek; Anafora; Language and languages -- Philosophy; Description (Philosophy); Anaphora (Linguistics); Language -- Philosophy